2015
DOI: 10.1016/j.jag.2015.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Detecting understory plant invasion in urban forests using LiDAR

Abstract: a b s t r a c tLight detection and ranging (LiDAR) data are increasingly used to measure structural characteristics of urban forests but are rarely used to detect the growing problem of exotic understory plant invaders. We explored the merits of using LiDAR-derived metrics alone and through integration with spectral data to detect the spatial distribution of the exotic understory plant Ligustrum sinense, a rapidly spreading invader in the urbanizing region of Charlotte, North Carolina, USA. We analyzed regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 57 publications
0
42
1
2
Order By: Relevance
“…Fuentes, Gamon, Qiu, Sims, and Roberts (2001) used AVIRIS-derived pigment and water absorption to map vegetation types in Canadian boreal forests and Kokaly, Despain, Clark, and Livo (2003) mapped forest cover types from the analysis of chlorophyll and leaf water absorption derived from AVIRIS imagery in Yellowstone National Park. In addition, forest structure variables estimated from lidar data such as aboveground/foliar biomass, stand basal area, diameter, height, crown length and crown width (Hawbaker et al, 2010;Lefsky, Cohen, Parker, & Harding, 2002;Lim, Treitz, Baldwin, Morrison, & Green, 2003;Muss, Mladenoff, & Townsend, 2011;Naesset, 2004) have been related to canopy species (Korpela, Orka, Maltamo, Tokola, & HyyppĂ€, 2010) and understory plant abundance (Singh, Davis, & Meentemeyer, 2015). In this study, we present an approach to map gradients of composition in lieu of composition or specific assemblages as a basis for understanding the functional composition of forests in urban ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Fuentes, Gamon, Qiu, Sims, and Roberts (2001) used AVIRIS-derived pigment and water absorption to map vegetation types in Canadian boreal forests and Kokaly, Despain, Clark, and Livo (2003) mapped forest cover types from the analysis of chlorophyll and leaf water absorption derived from AVIRIS imagery in Yellowstone National Park. In addition, forest structure variables estimated from lidar data such as aboveground/foliar biomass, stand basal area, diameter, height, crown length and crown width (Hawbaker et al, 2010;Lefsky, Cohen, Parker, & Harding, 2002;Lim, Treitz, Baldwin, Morrison, & Green, 2003;Muss, Mladenoff, & Townsend, 2011;Naesset, 2004) have been related to canopy species (Korpela, Orka, Maltamo, Tokola, & HyyppĂ€, 2010) and understory plant abundance (Singh, Davis, & Meentemeyer, 2015). In this study, we present an approach to map gradients of composition in lieu of composition or specific assemblages as a basis for understanding the functional composition of forests in urban ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have used data from active sensor, mainly LIDAR data, to map understory plants in boreal forests [16,17]. Combinations of LIDAR data and hyperspectral images were used to map understory invasive species in tropical forests [9], and the use of LIDAR data and high-resolution IKONOS imagery to identify understory plant invasion in urban forests [18]. Nevertheless, there are limitations on the use of these data due to its high cost and low availability, mainly in developing countries [19].…”
Section: Introductionmentioning
confidence: 99%
“…While most recent studies agree that the combination of satellite imagery and LiDAR data can lead to higher estimation accuracy, a publication by Singh et al [64] challenges this consensus. The authors found that with the help of a random forest classification method, LiDAR-derived topography metrics could detect understory plant invasion in urban forests with the highest accuracy, exceeding IKONOS data by 17.5% and combined LiDAR and IKONOS data by 5.3%.…”
Section: Satellite Imagery and Airborne Lidarmentioning
confidence: 99%